Penerapan Teknologi Digital dalam Pembinaan Remaja Gereja di Era Modern - Reja Banjarnahor; Shintia Barutu; Dearma Damanik (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The development of digital technology provides new opportunities in the development of church youth in the modern era. Youth as a digital generation are more responsive to technology-based approaches, so the church needs to adapt its development methods. This study aims to examine the application of digital technology in youth development strategies in the church environment. The method used is descriptive qualitative through field observations, in-depth interviews with church administrators and youth, and documentation studies of digital programs that have been implemented. The results of the study show that the use of social media, spiritual podcasts, development videos, and community-based digital applications can significantly increase youth participation and involvement. However, the study also found obstacles such as limited human resources, lack of digital training, and the absence of a systematic digital strategy. In conclusion, digital technology has great potential as a youth development tool if it is designed and implemented with a mature strategy and is oriented towards the needs of today's youth.